Overriding in Teams: The Role of Beliefs, Social Image, and Gender - Guo, Joyce; Recalde, María P. (Management Science, 2023)
To shed light on the factors that affect who speaks up in teams in the workplace, we study willingness to speak up after someone has raised an opinion. We call voicing disagreement overriding and study this behavior in a laboratory experiment where participants answer multiple choice questions in pairs. In a control treatment, participants interact anonymously. In a photo treatment, both participants see the photo of the person they are matched with at the beginning of the group task. Using a series of incentivized tasks, we elicit beliefs about the likelihood that each possible answer option to a question is correct. This allows us to measure disagreement and to tease apart the role of disagreement versus preferences in the decision to override ideas in teams. Results show that anonymity increases overriding. This treatment effect is driven by social image costs. Analysis of heterogeneity in behavior by gender reveals no differences between the likelihood that men and women override. However, we find some evidence that men and women are treated differently; when participants disagree with their partner, they are more likely to override a woman than a man. Preferences seem to in part explain the differential treatment of men and women. Studying group performance, we find that overriding helps groups on average, while the gender composition of teams does not affect team performance. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: This work was supported by the University of Melbourne and the Australian Research Council [Grant DE190100585]. J. Guo received a Kinsman Studentship from the University of Melbourne to conduct this research. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.4434 .